Positive pole piece, battery monomer, battery and electric device

By using polar functional groups and amorphous polymer binder in the positive electrode film layer of the lithium-ion battery, the problems of high brittleness and fracture of the positive electrode sheet are solved, and the performance and energy density of the battery are improved.

CN119230718APending Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310798013.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The positive electrode sheet of lithium-ion batteries is prone to high brittleness and fracture during production and use, which affects battery performance.

Method used

By using a first binder including polar functional groups, inorganic fillers and amorphous polymer in the positive electrode film layer, the crystallinity thereof is reduced, the non-forming region and amorphous properties are increased, thereby improving the flexibility of the positive electrode sheet. Reduce the possibility of breakage.

Benefits of technology

It effectively reduces the brittleness and fracture probability of the positive electrode sheet, and improves the performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230718A_ABST
    Figure CN119230718A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a positive pole piece, a battery monomer, a battery and an electric device. The positive pole piece comprises a positive current collector and a positive film layer arranged on at least one side of the positive current collector, wherein the positive film layer comprises a positive active material and a first binder; the first binder comprises at least one of a polar functional group except fluorine or a first substance; wherein the first substance comprises an inorganic filler and an amorphous polymer. According to the technical scheme, the crystallinity of the first binder and the slurry viscosity of the positive electrode film layer can be reduced, so that the brittleness of the positive electrode plate is reduced, the possibility of breakage of the positive electrode plate is reduced, and the battery performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and more specifically, to a positive electrode sheet, a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have been used in more and more fields, such as energy storage power supply fields such as wind power, hydropower, thermal power generation and solar power stations, as well as electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, etc. While lithium-ion batteries have made great progress, higher requirements have been put forward for their performance in all aspects.

[0003] Therefore, how to improve the performance of lithium-ion batteries is an urgent problem to be solved. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode sheet, a battery cell, a battery and an electrical device, which reduce the crystallinity of the first binder and the slurry viscosity of the positive electrode film layer, thereby reducing the brittleness of the positive electrode sheet and the possibility of the positive electrode sheet breaking, which is beneficial to improving battery performance.

[0005] The first aspect of the present application provides a positive electrode plate, comprising: a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, the positive electrode film layer comprising a positive electrode active material and a first binder, the first binder comprising at least one of a polar functional group or a first substance; wherein the first substance comprises an inorganic filler and an amorphous polymer.

[0006] In the embodiment of the present application, the positive electrode sheet includes a positive current collector and a positive electrode film layer, and the positive electrode film layer includes a positive electrode active material and a first binder; further, the first binder includes at least one of a polar functional group or a first substance, wherein the first substance includes an inorganic filler and an amorphous polymer. By including a polar functional group in the first binder, the polar functional group will destroy the integrity of the original chain segment in the first binder, thereby reducing the crystallinity of the first binder, making the first binder have a lower crystallinity and inhibiting the crystallinity of the first binder, and improving the flexibility of the positive electrode sheet; adding an inorganic filler and an amorphous polymer to the first binder, the inorganic filler and the amorphous polymer can increase the amorphous area and amorphousness of the first binder, thereby making the first binder have a lower crystallinity and improving the flexibility of the positive electrode sheet. Therefore, by making the first binder include polar functional groups, and / or including inorganic fillers and amorphous polymers, the first binder can have a lower degree of crystallinity, thereby reducing the brittleness of the positive electrode sheet, the possibility of fracture of the positive electrode sheet and improving the flexibility of the positive electrode sheet, which is beneficial to improving the performance of the battery.

[0007] In a possible implementation, the first binder includes the first substance and a second binder; wherein the second binder includes a fluorine-containing segment.

[0008] In the embodiment of the present application, the first binder includes polar functional groups, and / or includes inorganic fillers and amorphous polymers, so that the first binder can have a lower crystallinity. When the first binder includes the first substance, the first binder also includes a second binder, and the second binder includes a fluorine-containing segment, that is, the second binder containing a fluorine segment, an inorganic filler and an amorphous polymer are mixed to form the first binder, so that the amorphous region and amorphousness of the second binder can be increased, the crystallinity of the second binder can be reduced, and the final first binder has a lower crystallinity, thereby reducing the brittleness of the positive electrode sheet, the possibility of fracture, and improving the flexibility of the positive electrode sheet.

[0009] In one possible embodiment, the inorganic filler includes at least one of an oxide, a non-oxide with a dielectric constant greater than 3, and a non-oxide capable of transmitting active ions. Optionally, the inorganic filler includes at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate.

[0010] In an embodiment of the present application, by using at least one of an oxide or a non-oxide with a dielectric constant greater than 3 and a non-oxide with the ability to transport active ions as the second substance added to the positive electrode film layer, especially at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate, the crystallinity of the first binder can be reduced to reduce the possibility of breakage of the positive electrode plate during the production process.

[0011] In a possible implementation, the amorphous polymer includes at least one of methyl methacrylate and polyvinyl pyrrolidone.

[0012] In the embodiment of the present application, by using at least one of methyl methacrylate and polyvinyl pyrrolidone as the second substance added to the positive electrode film layer, the crystallinity of the first binder can be reduced to reduce the possibility of the positive electrode plate breaking during the production process.

[0013] In a possible implementation, the first binder includes a second binder substituted with a polar functional group at any position; wherein the second binder includes a fluorine-containing segment, and the second substance includes a polar functional group.

[0014] In the embodiment of the present application, the first binder includes polar functional groups, and / or includes inorganic fillers and amorphous polymers, which can reduce the first binder and keep it at a low crystallinity. The first binder is formed by a substitution reaction between the second binder and the second substance, wherein the second binder includes a fluorine-containing segment and the second substance includes a polar functional group. The polar functional group replaces any element on the first binder, or is grafted on any segment of the first binder, which can reduce the integrity of the fluorine-containing segment and reduce the proportion of the F element in the entire substance, thereby reducing the crystallinity of the second binder and inhibiting the degree of crystallization of the second binder, so that the final first binder has a lower crystallinity and improves the flexibility of the positive electrode sheet.

[0015] In a possible embodiment, the second substance includes at least one of polyethers, lipids, and vinyls. Optionally, the second substance includes at least one of polyethers and lipids. Optionally, the second substance includes at least one of polyethylene oxide, phthalate, and polypropylene oxide-polyethylene oxide.

[0016] In the embodiment of the present application, by using at least one of polyethers, lipids or vinyls as the second substance, a first binder is formed after a substitution reaction with the second binder containing a fluorine segment, and the first binder is added to the positive electrode film layer. This can reduce the crystallinity of the second binder and improve the bonding performance of the second binder, thereby reducing the possibility of the positive electrode film layer falling off and the positive electrode plate breaking. In particular, when at least one of oxygen-containing polyethers or lipids is used as the second substance, the introduced oxygen-containing groups can also dissociate the metal ions in the electrolyte and form a complex reaction, thereby promoting the transmission of metal ions in the battery, thereby further improving the performance of the battery.

[0017] In a possible implementation manner, the mass ratio of the first substance or the second substance to the second binder is 0.005-0.2. Optionally, the mass ratio of the first substance or the second substance to the second binder is 0.05-0.2.

[0018] In the above scheme, by limiting the mass ratio of the first substance or the second substance to the second adhesive to 0.005-0.2, especially 0.05-0.2, the first substance or the second substance can play its role and reduce the crystallinity of the second adhesive without affecting the bonding performance of the second adhesive.

[0019] In a possible implementation manner, the crystallinity of the first binder is 15%-45%. Optionally, the crystallinity of the first binder is 20%-40%.

[0020] In the embodiment of the present application, by making the crystallinity of the first binder 15%-45%, especially 20%-40%, the occurrence of agglomeration and condensation of the positive electrode film can be alleviated, thereby reducing the brittleness of the positive electrode sheet and reducing the probability of the positive electrode sheet breaking.

[0021] In a possible embodiment, the second binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Optionally, the second binder includes polyvinylidene fluoride.

[0022] In the embodiments of the present application, by using at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin as the second binder, the positive electrode plate has good bonding performance and can reduce the probability of the positive electrode film layer falling off; especially when polyvinyl fluoride is used as the second binder, polyvinylidene fluoride has two crystal forms, α and β, and inorganic substances and amorphous polymers are added to the positive electrode film layer. The inorganic substances and amorphous polymers can promote the α crystal form in polyvinylidene fluoride to convert to the β crystal form, thereby significantly reducing the crystallinity of polyvinylidene fluoride, and polyvinylidene fluoride has the strongest toughness and low price, which is conducive to further improving battery performance and being widely used in large-scale applications.

[0023] In one possible implementation, the positive electrode active material Li a Ni x Co y M 1-x-y O 2-b , wherein M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg and Nb, optionally, M includes at least one of Mn, Al, B, Zr, Sr, W, Mg and Nb; 0.2≤a≤1.2, 0≤b≤0.2; 0.85≤x≤1, 0≤y≤0.15, optionally, 0.92≤x≤0.98, 0<y≤0.08.

[0024] In the embodiments of the present application, by using an ultra-high nickel material satisfying the above chemical formula as the positive electrode active material of the battery, it is beneficial to further improve the energy density of the battery.

[0025] In a possible implementation, the mass ratio of the residual alkali on the surface of the positive electrode active material to the positive electrode active material is 0.0001-0.05. Optionally, the mass ratio of the residual alkali on the surface of the positive electrode active material to the positive electrode active material is 0.0001-0.03.

[0026] In an embodiment of the present application, when an ultra-high nickel material is used as the positive electrode active material of the battery, the surface residual alkali present on the surface of the ultra-high nickel material will cause chemical gelation if it is in direct contact with the second binder containing a fluorine segment. Therefore, in the positive electrode film layer, using a first binder with polar functional groups grafted on the main chain of the second binder, or using a second binder, an inorganic filler and an amorphous polymer mixed as the first binder, can reduce the probability of direct contact between the surface residual alkali and the binder, thereby reducing the chemical gelation caused by direct contact between the two. However, if the amount of surface residual alkali is too high, condensation will still occur in the positive electrode film layer. Therefore, by limiting the mass fraction of the surface residual alkali of the positive electrode active material in the positive electrode active material to 0.01%-5%, especially 0.01%-3%, the chemical gelation of the positive electrode film slurry can be effectively prevented.

[0027] In a possible implementation, when the positive electrode sheet is folded four times, the ratio of the light-transmitting length of the fold of the positive electrode sheet to the length of the fold of the positive electrode sheet is 0-0.2. Optionally, the ratio of the light-transmitting length of the fold of the positive electrode sheet to the length of the fold of the positive electrode sheet is 0-0.1.

[0028] In the embodiment of the present application, in the case of a four-fold positive electrode sheet, the ratio of the light-transmitting length of the fold of the positive electrode sheet to the fold length is limited to 0-0.2, especially 0-0.1, which indicates that the positive electrode sheet has good mechanical properties and is relatively less likely to break during use.

[0029] In a possible implementation manner, the slurry viscosity of the positive electrode film layer is 3000-20000 MPa·s. Optionally, the slurry viscosity of the positive electrode film layer is 5000-12000 MPa·s.

[0030] In the embodiment of the present application, by limiting the slurry viscosity of the positive electrode film layer to 3000-20000 MPa·s, especially 5000-12000 MPa·s, the positive electrode film layer not coated on the positive electrode current collector can maintain good flow properties, thereby reducing the possibility of chemical gelation of the positive electrode film layer.

[0031] In one possible embodiment, the coating weight of the positive electrode sheet is 20-50 mg / cm 2 Optionally, the coating weight of the positive electrode sheet is 25-45 mg / cm 2 .

[0032] In the embodiment of the present application, the coating weight of the positive electrode sheet is limited to 20-50 mg / cm 2 , especially 25-45mg / cm 2 , which can improve the energy density of the battery.

[0033] In one possible implementation, the compaction density of the positive electrode sheet is 3-4 g / cm 3 Optionally, the compaction density of the positive electrode sheet is 3.2-3.6 g / cm 3 .

[0034] In the embodiment of the present application, the compaction density of the positive electrode sheet is limited to 3-4 g / cm 3 , especially 3.2-3.6g / cm 3 , which is beneficial to improve the energy density of the battery.

[0035] The second aspect of the present application provides a method for preparing a positive electrode plate, comprising: providing a positive electrode current collector; arranging a positive electrode film layer on at least one side of the positive electrode current collector, the positive electrode film layer comprising a positive electrode active material and a first binder, the first binder comprising at least one of a polar functional group other than fluorine or a first substance; wherein the first substance comprises an inorganic filler and an amorphous polymer.

[0036] In a possible implementation, the first substance and a second binder are provided, and the second binder includes a fluorine-containing segment.

[0037] In one possible embodiment, the inorganic filler includes at least one of an oxide, a non-oxide with a dielectric constant greater than 3, and a non-oxide capable of transmitting active ions. Optionally, the inorganic filler includes at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate.

[0038] In a possible implementation, the amorphous polymer includes at least one of polymethyl methacrylate and polyvinyl pyrrolidone.

[0039] In a possible implementation, a second binder and a second substance are provided, and a substitution reaction occurs between the second binder and the second substance; wherein the second binder includes a fluorine-containing segment, and the second substance includes a polar functional group.

[0040] In a possible embodiment, the second substance includes at least one of polyethers, lipids, and vinyls. Optionally, the second substance includes at least one of polyethers and lipids. Optionally, the second substance includes at least one of polyethylene oxide, phthalate, and polypropylene oxide-polyethylene oxide.

[0041] In a possible implementation manner, the mass ratio of the first substance or the second substance to the second binder is 0.005-0.2. Optionally, the mass ratio of the first substance or the second substance to the second binder is 0.05-0.2.

[0042] In a possible embodiment, the second binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Optionally, the second binder includes polyvinylidene fluoride.

[0043] The third aspect of the present application provides a battery cell, comprising the positive electrode sheet described in any embodiment of the first aspect of the present application or the positive electrode sheet prepared by the method for preparing the positive electrode sheet described in any embodiment of the second aspect.

[0044] The fourth aspect of the present application provides a battery, comprising the battery cell described in the third aspect of the present application.

[0045] The fifth aspect of the present application provides an electrical device, comprising the battery according to the fourth aspect of the present application, wherein the battery is used to provide electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0047] Figure 1 This is a schematic structural diagram of a positive electrode sheet according to an embodiment of the present application;

[0048] Figure 2 This is a flow chart of a method for preparing a positive electrode sheet according to an embodiment of the present application;

[0049] Figure 3 A schematic diagram of a battery cell according to an embodiment of the present application;

[0050] Figure 4 A schematic diagram of the structure of a battery cell according to an embodiment of the present application;

[0051] Figure 5 A schematic diagram of a battery according to an embodiment of the present application;

[0052] Figure 6 A schematic diagram of the structure of a battery according to one embodiment of the present application;

[0053] Figure 7 It is a schematic structural diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION

[0054] The following describes the embodiments of the positive electrode sheet, battery cell, battery and electric device of the present application in detail with appropriate reference to the drawings, but there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0055] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a specific range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0058] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, and can be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or comprised.

[0060] The terms "above", "below", "greater than" or "less than" as used in this application include the number, for example, "at least one" means one or more, and "at least one of A and B" means "A", "B" or "A and B".

[0061] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0062] Lithium batteries are widely used in consumer electronics due to their high energy density, high power and long cycle performance. In recent years, with the continuous development of electric vehicles and energy storage systems, people's requirements for battery performance in all aspects are also increasing.

[0063] In order to improve the energy density of the battery, most of the existing technologies coat more positive active materials on the positive current collector, which results in a thicker positive electrode sheet. In other words, the high energy density lithium battery system requires a thick film electrode design for the positive electrode. However, during the processing and use of the battery, the thick film electrode often has a large brittle electrode sheet, which will cause the electrode sheet to break and seriously damage the performance of the battery. Therefore, how to reduce the probability of thick film electrode sheet breakage during battery production and use is an urgent problem to be solved.

[0064] In view of this, the present application provides a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, the positive electrode film layer includes a positive electrode active material and a first binder; the first binder includes at least one of a polar functional group or a first substance; wherein the first substance includes an inorganic filler and an amorphous polymer. The first binder has a low crystallinity, and the positive electrode sheet containing the binder has a low brittleness, a low probability of fracture during the production process, and is conducive to improving battery performance.

[0065] The positive electrode sheet, battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.

[0066] In addition, the technical solution of the present application is applicable to various types of batteries such as lithium-ion batteries, lithium metal batteries, sodium-ion batteries, etc., and the present application does not limit this; for the sake of description, the following description will take lithium-ion batteries as an example.

[0067] [Positive electrode]

[0068] The first aspect of the present application provides a positive electrode plate, Figure 1 Schematic diagram of the structure of the positive electrode sheet of one embodiment of the present application. Figure 1 As shown, the positive electrode plate 121 includes a positive electrode collector 122 and a positive electrode film layer 123 arranged on at least one side of the positive electrode collector 122, and the positive electrode film layer 123 includes a positive electrode active material and a first binder; wherein the first binder includes at least one of a polar functional group or a first substance; wherein the first substance includes an inorganic filler and an amorphous polymer.

[0069] The use of at least one of polar functional groups or inorganic fillers and amorphous polymers in the positive electrode film layer 123 can reduce the brittleness and possibility of fracture of the positive electrode sheet 121 .

[0070] Typically, a battery cell includes a positive electrode sheet 121, a separator, a negative electrode sheet, and an electrolyte. During the battery charge and discharge process, active ions are embedded and released back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0071] The “positive electrode sheet” and “negative electrode sheet” mentioned in the embodiments of the present application refer to the positive electrode sheet and the negative electrode sheet as a whole including active materials, current collectors or other additives.

[0072] The positive electrode sheet 121 includes a positive electrode current collector 122 and a positive electrode film layer 123 disposed on at least one surface of the positive electrode current collector 122 , wherein the positive electrode film layer 123 includes a positive electrode active material.

[0073] As an example, the positive electrode current collector 122 has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer 123 is disposed on any one or both of the two opposite surfaces of the positive electrode current collector 122 .

[0074] Polar functional groups refer to functional groups whose positive and negative charge centers do not overlap. The polarity of the functional group can be characterized by a dipole moment; the polarity of the polar functional group can be weak polarity, polarity, or strong polarity. The polar functional group here can be a carbon-carbon double bond, a carbon-carbon triple bond, a hydroxyl group, a carboxyl group, an ether bond, an aldehyde group, a carbonyl group, and the like.

[0075] Inorganic fillers refer to inorganic substances as the filling material; inorganic substances usually refer to compounds that do not contain carbon elements, but include carbon-containing carbon oxides, carbonates, cyanides, carbides, carboranes, carbonyl metals, alkyl metals, metal organic ligand complexes, etc., which are carbon-containing species studied in inorganic chemistry. It is a general term for simple substances and inorganic compounds. For example, inorganic substances can be silicon dioxide, lithium niobate, calcium carbonate, etc.

[0076] Amorphous polymers refer to polymers whose molecular shapes and molecular arrangements are in a disordered state. For example, amorphous polymers may be polymethyl methacrylate (PMMA) or polyvinyl pyrrolidone (PVP).

[0077] In the embodiment of the present application, the positive electrode sheet 121 includes a positive electrode current collector 122 and a positive electrode film layer 123, and the positive electrode film layer 123 includes a positive electrode active material and a first binder; further, the first binder includes at least one of a polar functional group or a first substance, wherein the first substance includes an inorganic filler and an amorphous polymer. By including a polar functional group in the first binder, the polar functional group will destroy the integrity of the original binder segment, thereby making the first binder have a lower crystallinity and inhibiting the crystallization degree of the first binder, and improving the flexibility of the positive electrode sheet 121; adding an inorganic filler and an amorphous polymer to the first binder, the inorganic filler and the amorphous polymer can increase the amorphous region and amorphousness of the first binder, thereby making the first binder have a lower crystallinity and improving the flexibility of the positive electrode sheet. Therefore, by making the first binder include polar functional groups, and / or including inorganic fillers and amorphous polymers, the first binder can have a lower degree of crystallinity, thereby reducing the brittleness of the positive electrode sheet, the possibility of fracture of the positive electrode sheet and improving the flexibility of the positive electrode sheet, which is beneficial to improving the performance of the battery.

[0078] In some embodiments, the first binder includes a first substance and a second binder; wherein the second binder includes a fluorine-containing segment.

[0079] The fluorinated chain segment is a molecular chain segment containing fluorine atoms.

[0080] The first binder is a binder obtained by modifying the second binder.

[0081] In the above scheme, the first binder includes a polar functional group, and / or includes an inorganic filler and an amorphous polymer, so that the first binder has a lower crystallinity. When the first binder includes the first substance, the first binder also includes a second binder, and the second binder includes a fluorine-containing segment, that is, the second binder containing a fluorine segment, an inorganic filler and an amorphous polymer are mixed to form the first binder, so that the amorphous region and amorphousness of the second binder can be increased, the crystallinity of the second binder can be reduced, and the final first binder has a lower crystallinity, thereby reducing the brittleness of the positive electrode sheet 121, the possibility of fracture, and improving the flexibility of the positive electrode sheet 121.

[0082] It should be noted here that when the crystallinity of the first binder or the second binder is reduced by adding the first substance, the first substance and the second binder can be directly mixed and then added to the positive electrode film layer 123; or the first substance and the second binder can be added to the positive electrode film layer 123 in sequence, and the present application does not limit this.

[0083] In addition, mixing the second binder with the first substance to form the first binder together can reduce the crystallinity of the second binder so that the first binder has a lower crystallinity. It can also be directly said that the crystallinity of the first binder is reduced because the first binder is a modified second binder in which the second binder still plays a bonding role.

[0084] In some embodiments, the inorganic filler includes at least one of an oxide, a non-oxide with a dielectric constant greater than 3, and a non-oxide capable of transporting active ions. Optionally, the inorganic filler includes at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate.

[0085] Oxides are compounds containing the element oxygen.

[0086] The dielectric constant characterizes the ability of the electrolyte to bind charges. The larger the dielectric constant, the better the insulation performance of the material.

[0087] In the above scheme, by using at least one of an oxide or a non-oxide with a dielectric constant greater than 3, and a non-oxide with the ability to transport active ions as the second substance added to the positive electrode film layer, especially at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate, the crystallinity of the first binder can be effectively reduced to reduce the possibility of breakage of the positive electrode plate during the production process.

[0088] In some embodiments, the inorganic filler can also be boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n TinO3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 ) 3- At least one of PbTiO3 (abbreviated as PMN-PT).

[0089] In some embodiments, the inorganic filler may also be lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Tiy(PO4)3,0<x<2,0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass (0<x<4, 0<y<13), lanthanum lithium titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).

[0090] In some embodiments, the amorphous polymer includes at least one of methyl methacrylate and polyvinyl pyrrolidone.

[0091] In the above solution, by using at least one of methyl methacrylate and polyvinyl pyrrolidone as the second substance added to the positive electrode film layer 123, the crystallinity of the binder can be reduced to reduce the possibility of the positive electrode plate 121 breaking during the production process.

[0092] In some embodiments, the first binder includes a second binder substituted with a polar functional group at any position; wherein the second binder includes a fluorine-containing segment, and the second substance includes a polar functional group.

[0093] In the above scheme, the first binder includes polar functional groups, and / or includes inorganic fillers and amorphous polymers, which can reduce the first binder and keep it at a low crystallinity. The first binder is formed by a substitution reaction between the second binder and the second substance, wherein the second binder includes a fluorine-containing segment and the second substance includes a polar functional group. The polar functional group replaces any element on the first binder, or is grafted on any segment of the first binder, which can reduce the integrity of the fluorine-containing segment and reduce the proportion of the F element in the entire substance, thereby reducing the crystallinity of the second binder and inhibiting the degree of crystallization of the second binder, so that the final first binder has a lower crystallinity and improves the flexibility of the positive electrode sheet.

[0094] It should be noted that the second substance and the second binder undergo a substitution reaction to graft the polar functional group in the second substance into the second binder. Wherein, the polar functional group grafted onto the second binder means that the polar functional group can be directly grafted onto any molecular chain of the second binder, or can replace an atom of the second binder, and this application does not limit this. As long as the polar functional group is added to the structure of the second binder, the crystallinity of the second binder can be reduced.

[0095] In addition, the second substance containing polar functional groups will destroy the integrity of the fluorine-containing segment, involving chemical reactions, so the second substance and the second binder may need to undergo a substitution reaction under certain conditions and then be added to the positive electrode film layer 123. For example, when the binder of the fluorine-containing segment is polyvinylidene fluoride and the compound containing polar functional groups is styrene, the two should be mixed together in an N,N-dimethylformamide (DMF) solution and polymerized by heating. The specific polymerization conditions of the second binder and the first substance containing polar functional groups depend on the specific substances, and this application does not limit this.

[0096] In addition, allowing the second adhesive to undergo a substitution reaction with the second substance to form the first adhesive can be said to reduce the crystallinity of the second adhesive so that the first adhesive has a lower crystallinity. It can also be directly said that the crystallinity of the first adhesive is reduced because for the first adhesive, it is still the second adhesive that plays a bonding role.

[0097] In some embodiments, the first substance includes at least one of polyethers, lipids, and vinyls. Optionally, the first substance includes at least one of polyethers and lipids. Optionally, the second substance includes at least one of polyethylene oxide, phthalate, and polypropylene oxide-polyethylene oxide.

[0098] In the above scheme, by using at least one of polyethers, lipids or vinyls as the first substance, a substitution reaction is carried out with the second binder containing fluorine segments to form a first binder, and the first binder is added to the positive electrode film layer 123. This can reduce the crystallinity of the second binder and improve the bonding performance of the second binder, thereby reducing the possibility of the positive electrode film layer 123 falling off and the positive electrode plate 121 breaking. In particular, when at least one of oxygen-containing polyethers or lipids is used as the second substance, the introduced oxygen-containing groups can also dissociate the metal ions in the electrolyte and form a complex reaction, thereby promoting the transmission of metal ions in the battery, thereby further improving the performance of the battery.

[0099] In some embodiments, the mass ratio of the first substance or the second substance to the second binder is 0.005-0.2. Optionally, the mass ratio of the first substance or the second substance to the second binder is 0.05-0.2.

[0100] In the above scheme, by limiting the mass ratio of the first substance or the second substance to the second adhesive to 0.005-0.2, especially 0.05-0.2, the first substance or the second substance can play its role and reduce the crystallinity of the second adhesive without affecting the bonding performance of the second adhesive.

[0101] In some embodiments, the crystallinity of the first binder is 15%-45%. Optionally, the crystallinity of the first binder is 20%-40%.

[0102] Crystallinity is used to indicate the proportion of crystalline regions in a polymer. Generally, the higher the crystallinity, the more regular the molecular chains are arranged. Materials with high crystallinity crystallize faster, are more brittle, have poor toughness and ductility, and are also prone to breakage.

[0103] In the above scheme, by making the crystallinity of the first binder 15%-45%, especially 20%-40%, the agglomeration and condensation of the positive electrode film 123 can be alleviated, thereby reducing the brittleness of the positive electrode sheet 121 and the probability of the positive electrode sheet 121 breaking.

[0104] In some embodiments, the second binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Optionally, the second binder includes polyvinylidene fluoride.

[0105] In the above scheme, by using at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin as the second binder, the positive electrode plate 121 has good bonding performance and can reduce the probability of the positive electrode film layer 123 falling off; especially when polyvinylidene fluoride is used as a binder, polyvinylidene fluoride has two crystal forms, α and β. Inorganic substances and amorphous polymers are added to the positive electrode film layer 123. The inorganic substances and amorphous polymers can promote the α crystal form in polyvinylidene fluoride to transform into the β crystal form, thereby significantly reducing the crystallinity of polyvinylidene fluoride. Polyvinylidene fluoride has the strongest toughness and is low in price, which is conducive to further improving battery performance and being widely used in large-scale applications.

[0106] In some embodiments, the positive electrode active material includes Li a Ni x Co y M 1-x-y O 2-b , wherein M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg and Nb, optionally, M includes at least one of Mn, Al, B, Zr, Sr, W, Mg and Nb; 0.2≤a≤1.2, 0≤b≤0.2; 0.85≤x≤1, 0≤y≤0.15, optionally, 0.92≤x≤0.98, 0<y≤0.08.

[0107] In the embodiments of the present application, by using an ultra-high nickel material satisfying the above chemical formula as the positive electrode active material of the battery, it is beneficial to further improve the energy density of the battery.

[0108] For example, ultra-high nickel materials include but are not limited to: LiNi 0.96 Co 0.01 Mn 0.03 O2、LiNi 0.96 Co 0.02 Mn 0.02 O2、LiNi 0.99 Co 0.005 Mn 0.005 O2, etc.

[0109] In some embodiments, the mass ratio of the residual alkali on the surface of the positive electrode active material to the positive electrode active material is 0.0001-0.05. Optionally, the mass ratio of the residual alkali on the surface of the positive electrode active material to the positive electrode active material is 0.0001-0.03.

[0110] In an embodiment of the present application, when an ultra-high nickel material is used as the positive electrode active material of the battery, the surface residual alkali on the surface of the ultra-high nickel material will cause chemical gelation if it is in direct contact with the binder containing fluorine segments. Therefore, in the positive electrode film layer 123, a binder with polar functional groups grafted on the main chain of the second binder, or a second binder, an inorganic filler and an amorphous polymer are used as a binder to reduce the probability of direct contact between the surface residual alkali and the binder, thereby reducing the chemical gelation caused by direct contact between the two. However, if the surface residual alkali is too high, condensation will still occur in the positive electrode film layer. Therefore, by limiting the mass fraction of the surface residual alkali of the positive electrode active material in the positive electrode active material to 0.01%-5%, especially 0.01%-3%, the chemical gelation of the positive electrode film layer 123 slurry can be effectively prevented.

[0111] In some embodiments, in the case of a four-folded positive electrode sheet 121, the ratio of the light-transmitting length of the fold of the positive electrode sheet 121 to the length of the fold of the positive electrode sheet 121 is 0-0.2. Optionally, the ratio of the light-transmitting length of the fold of the positive electrode sheet 121 to the length of the fold of the positive electrode sheet 121 is 0-0.1.

[0112] When the fold is transparent, the positive electrode film 123 at the fold is about to break, that is, the transparent part is also the breaking part. Therefore, if the positive electrode film 123 on the positive electrode sheet 121 is broken at multiple places, the entire positive electrode sheet 121 will be broken.

[0113] In the embodiment of the present application, in the case of a four-fold positive electrode sheet 121, by limiting the ratio of the light-transmitting length of the fold of the positive electrode sheet 121 to the fold length to 0-0.2, in particular to 0-0.1, it is indicated that the positive electrode sheet has good mechanical properties and is relatively less likely to break during use.

[0114] In some embodiments, the slurry viscosity of the positive electrode film layer 123 is 3000-20000 mpa·s. Optionally, the slurry viscosity of the positive electrode film layer 123 is 5000-12000 mpa·s.

[0115] The slurry viscosity refers to the viscosity of the slurry. The larger the value, the less likely it is to flow.

[0116] It should be noted that the slurry viscosity of the positive electrode film layer 123 here refers to the slurry viscosity before the positive electrode film layer 123 is coated on the positive electrode current collector 122 .

[0117] In the above scheme, by limiting the slurry viscosity of the positive electrode film layer 123 to 3000-20000 MPa·s, especially 5000-12000 MPa·s, the positive electrode film layer 123 not coated on the positive electrode current collector 122 can maintain good flow properties, thereby reducing the possibility of chemical gelation of the positive electrode film layer 123.

[0118] In some embodiments, the coating weight of the positive electrode sheet 121 is 20-50 mg / cm 2 Optionally, the coating weight of the positive electrode sheet 121 is 25-45 mg / cm 2 .

[0119] In the embodiment of the present application, the coating weight of the positive electrode sheet 121 is limited to 20-50 mg / cm 2 , especially 25-45mg / cm 2 , which can improve the energy density of the battery.

[0120] The coating weight of the positive electrode sheet 121 can be 25 mg / cm 2 、30mg / cm 2 , 40mg / cm 2 , 45mg / cm 2 and any value within the range consisting of the above values.

[0121] In a possible implementation, the compaction density of the positive electrode sheet 121 is 3-4 g / cm 3 Optionally, the compaction density of the positive electrode sheet 121 is 3.2-3.6 g / cm 3 .

[0122] In the embodiment of the present application, the compaction density of the positive electrode sheet 121 is limited to 3-4 g / cm 3 , especially 3.2-3.6g / cm 3 , which is beneficial to improve the energy density of the battery.

[0123] The compaction density of the positive electrode sheet 121 can be 3 g / cm 3 、3.2g / cm 3 , 3.5g / cm 3 and any value within the range consisting of the above values.

[0124] In some embodiments, the positive electrode current collector 122 may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0125] In some embodiments, as an example, the positive electrode active material may also be a lithium-containing phosphate including an olivine structure and its modified product or a lithium transition metal oxide and its modified compound. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.

[0126] In some embodiments, examples of lithium transition metal oxides may include, but are not limited to, materials with layered structures and materials with spinel structures. The layered materials include lithium cobalt oxide (such as LiCoO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt manganese oxide Li p Ni a Co b Mn 1-a-b O2 (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), lithium nickel cobalt aluminum oxide Li p Ni c Co d Al 1-c-d O2 (such as LiNi 0.85 Co 0.15 Al 0.05 O2), nLi2MnO3·(1-n)LiM2O2, wherein 0.2≤p≤1.2, 0<a<1, 0<b<1, 0<a+b<1, 0<c<1, 0<d<1, 0<c+d<1, 0<n<1, M2 comprises at least one of Co, Ni, and Mn. The spinel structure material comprises LiMn2O4, LiNi e Mn 2-e At least one of O4, wherein 0<e<2.

[0127] In some embodiments, the olivine structured material may include Li q Fe 1-x-y Mn x M1y PO4, 0.1≤p≤1.15, 0≤x≤1, 0≤y<1, 0≤x+y≤1, M1 includes at least one of other transition metal elements or non-transition metal elements except Fe and Mn; optionally, M1 includes at least one of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr. Examples of lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0128] It should be noted here that the battery will be accompanied by Li deintercalation and consumption during the charging and discharging process, and the molar content of Li is different when the battery is discharged to different states. In the above list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after the charge and discharge cycle.

[0129] In addition, in the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0130] In some embodiments, the positive electrode sheet 121 can be prepared by the following method: the components used to prepare the positive electrode sheet 121, such as LiNi 0.96 Co 0.01 Mn 0.03 O2, binder, modifier and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode film slurry (also called positive electrode active material slurry). The positive electrode film slurry is coated on the positive electrode collector 122. After drying, cold pressing and other processes, the positive electrode sheet 121 can be obtained.

[0131] Figure 2 This is a method for preparing a positive electrode sheet according to an embodiment of the present application. In some embodiments, Figure 2 As shown, the preparation method of the positive electrode plate 121 includes:

[0132] S201: providing a positive electrode current collector 122;

[0133] S202: disposing a positive electrode film layer on at least one side of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material and a first binder, wherein the first binder includes at least one of a polar functional group other than fluorine or a first substance;

[0134] The first substance includes an inorganic filler and an amorphous polymer.

[0135] In some embodiments, a first material and a second binder are provided, the second binder comprising a fluorine-containing segment.

[0136] In some embodiments, the inorganic filler includes at least one of an oxide, a non-oxide having a dielectric constant greater than 3, and a non-oxide capable of transporting active ions. Optionally, the inorganic filler includes at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate.

[0137] In some embodiments, the amorphous polymer includes at least one of polymethyl methacrylate and polyvinyl pyrrolidone.

[0138] In some embodiments, a second binder and a second substance are provided, and a substitution reaction occurs between the second binder and the second substance; wherein the second binder includes a fluorine-containing segment, and the second substance includes a polar functional group.

[0139] In some embodiments, the second substance includes at least one of polyethers, lipids, and vinyls. Optionally, the second substance includes at least one of polyethers and lipids. Optionally, the second substance includes at least one of polyethylene oxide, phthalate, and polypropylene oxide-polyethylene oxide.

[0140] In some embodiments, the amorphous polymer includes at least one of polymethyl methacrylate and polyvinyl pyrrolidone.

[0141] In some embodiments, the mass ratio of the first substance or the second substance to the second binder is 0.005-0.2. Optionally, the mass ratio of the first substance or the second substance to the second binder is 0.05-0.2.

[0142] In a possible embodiment, the second binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Optionally, the second binder includes polyvinylidene fluoride.

[0143] [Negative electrode]

[0144] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0145] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0146] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0147] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0148] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0149] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0150] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0151] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0152] [Electrolytes]

[0153] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0154] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0155] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0156] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0157] In some embodiments, the electrolyte may also optionally include negative electrode film-forming additives, positive electrode film-forming additives, and may also include performance additives that can improve certain battery properties, such as improving battery overcharge performance, improving battery high temperature or low temperature performance, etc.

[0158] [Isolation film]

[0159] The present application does not particularly limit the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.

[0160] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0161] In some embodiments, the positive electrode sheet 121 , the negative electrode sheet, and the separator may be formed into the electrode assembly 12 by a winding process or a lamination process.

[0162] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0163] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0164] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 3 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0165] Figure 4 FIG. 1 is a schematic diagram of the structure of a battery cell according to an embodiment of the present application. Figure 4 As shown, the outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet 121, the negative electrode sheet and the isolation film can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 100 can be one or more, and those skilled in the art can select according to specific actual needs.

[0166] In some embodiments, the battery cells 100 may also be assembled into a battery module. The battery module may contain one or more battery cells 100. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0167] In some embodiments, the battery cells 100 may also be directly assembled into a battery. The number of battery cells 100 contained in the battery may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery.

[0168] Figure 5 is a schematic diagram of a battery according to one embodiment of the present application, Figure 6 This is a schematic diagram of the structure of a battery according to one embodiment of the present application. Figure 5 and Figure 6 The battery 400 may include a battery box and a plurality of battery cells 100 disposed in the battery box. The battery box includes an upper box body 401 and a lower box body 402. The upper box body 401 can cover the lower box body 402 and form a closed space for accommodating the battery cells 100. The plurality of battery cells 100 may be arranged in the battery box in any manner.

[0169] In addition, the present application also provides an electric device, which includes at least one of the positive electrode sheet 121, battery cell 100 or battery 400 provided in the present application. The positive electrode sheet 121, battery cell 100 or battery 400 can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0170] For example, Figure 7 Schematic diagram of the structure of an electric device according to an embodiment of the present application. Figure 7 As shown, the power-consuming device 1 can be a vehicle 1, and the vehicle 1 can be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 500, a controller 600 and a battery 400 can be arranged inside the vehicle 1, and the controller 600 is used to control the battery 400 to supply power to the motor 500. For example, a battery 400 can be arranged at the bottom, front or rear of the vehicle 1. The battery 400 can be used to power the vehicle 1, for example, the battery 400 can be used as an operating power source for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power requirements during the start-up, navigation and operation of the vehicle 1. In another embodiment of the present application, the battery 400 can not only be used as an operating power source for the vehicle 1, but also as a driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.

[0171] As the electrical device, the positive electrode sheet 121 , the secondary battery cell 100 or the battery 400 may be selected according to its use requirements.

[0172] The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery cell 100 or a battery 400 may be used.

[0173] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and the battery cell 100 may be used as a power source.

[0174] [Example]

[0175] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0176] [Example 1]

[0177] 1). Preparation of lithium-ion batteries

[0178] 1.1) Preparation of the first binder: The second substance phthalate monomer and the second binder vinylidene fluoride monomer are mixed at a mass ratio of 1:10, dissolved in N,N-dimethylformamide (DMF) solution, fully mixed at 80°C and then dried the solvent; finally, an inert atmosphere is introduced, diisopropylbenzene peroxide is added, and the solution is heated to 100°C, fully and evenly stirred for 2 hours to achieve polymerization, and the first binder is prepared after removing the solvent. Among them, the mass ratio of the second substance to the second binder is 0.1.

[0179] 1.12) Preparation of positive electrode: 0.96 Co 0.01 Mn 0.03 O2, conductive carbon (SP), and the first binder are dissolved in a solvent N-methylpyrrolidone (NMP) in a mass ratio of 96%:2%:2%, and are fully stirred and mixed to prepare a positive electrode film slurry. The positive electrode film slurry is coated on the positive electrode collector aluminum foil, and then dried at 100°C, cold pressed at 40T, and cut to obtain a positive electrode sheet; wherein the mass ratio of the surface residual alkali of the positive electrode active material to the positive electrode active material is 0.02.

[0180] 1.2) Preparation of negative electrode: Active material artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a proper amount of deionized water solvent system in a weight ratio of 97.5%:0.7%:1.8%:1% to obtain negative electrode active material, and the negative electrode active material is coated on Cu foil, and then dried, cold pressed and cut to obtain negative electrode sheets.

[0181] 1.3). Preparation of diaphragm: PE porous polymer film is used as the isolation membrane.

[0182] 1.4). Electrolyte: Dissolve EC / EMC / DMC in 1M LiPF6 at a volume ratio of 1:1:1 and stir evenly.

[0183] 1.5) Assembly: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and wind them to get the electrode assembly, and add electrolyte. Then hot press at 100℃ and 250MPa for 2min to get the lithium-ion battery.

[0184] [Example 2]

[0185] The preparation process of the lithium ion battery of Example 2 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 2, the second binder is polytetrafluoroethylene (PTFE).

[0186] [Example 3]

[0187] The preparation process of the lithium ion battery of Example 3 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 3, the second binder is a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer.

[0188] [Example 4]

[0189] The preparation process of the lithium ion battery of Example 4 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 4, the second substance phthalate is replaced by the first substance silicon dioxide.

[0190] [Example 5]

[0191] The preparation process of the lithium ion battery of Example 5 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 5, the second substance phthalate is replaced by the first substances silicon dioxide and polymethyl methacrylate.

[0192] [Example 6]

[0193] The preparation process of the lithium ion battery of Example 6 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 6, the second substance phthalate is replaced by the first substances lithium niobate and polymethyl methacrylate.

[0194] [Example 7]

[0195] The preparation process of the lithium ion battery of Example 7 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 7, the second substance phthalate is replaced by the second substance polyethylene oxide.

[0196] [Example 8]

[0197] The preparation process of the lithium ion battery of Example 8 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 8, the second substance phthalate is replaced by the second substance styrene.

[0198] [Example 9]

[0199] The preparation process of the lithium ion battery of Example 9 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 9, the mass ratio of the first substance / the second substance to the second binder is 0.005.

[0200] [Example 10]

[0201] The preparation process of the lithium ion battery of Example 10 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 10, the mass ratio of the first substance / the second substance to the second binder is 0.05.

[0202] [Example 11]

[0203] The preparation process of the lithium ion battery of Example 11 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 11, the mass ratio of the first substance / the second substance to the second binder is 0.15.

[0204] [Example 12]

[0205] The preparation process of the lithium ion battery of Example 12 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 9, the mass ratio of the first substance / the second substance to the second binder is 0.2.

[0206] [Example 13]

[0207] The preparation process of the lithium ion battery of Example 13 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 13, the mass ratio of the first substance / the second substance to the second binder is 0.24.

[0208] [Example 14]

[0209] The preparation process of the lithium ion battery of Example 14 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 9, the mass ratio of the first substance / the second substance to the second binder is 0.3.

[0210] [Example 15]

[0211] The preparation process of the lithium ion battery of Example 15 is substantially the same as that of Example 5, except that in the lithium ion battery of Example 15, the mass ratio of the first substance / the second substance to the second binder is 0.005.

[0212] [Example 16]

[0213] The preparation process of the lithium ion battery of Example 16 is substantially the same as that of Example 5, except that in the lithium ion battery of Example 16, the mass ratio of the first substance / the second substance to the second binder is 0.005.

[0214] [Example 17]

[0215] The preparation process of the lithium ion battery of Example 17 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 17, the positive electrode active material is LiNi 0.98 Co 0.01 Mn 0.01 O2.

[0216] [Example 18]

[0217] The preparation process of the lithium ion battery of Example 18 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 18, the positive electrode active material is LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0218] [Example 19]

[0219] The preparation process of the lithium ion battery of Example 19 is substantially the same as that of Example 1, except that in the lithium ion battery of Example 19, the mass ratio of the surface residual alkali to the positive electrode active material is 0.05.

[0220] [Example 20]

[0221] The preparation process of the lithium-ion battery of Example 20 is substantially the same as that of Example 1, except that in the lithium-ion battery of Example 20, the mass ratio of the surface residual alkali to the positive electrode active material is 0.03.

[0222] [Comparative Example 1]

[0223] The preparation process of the lithium ion battery of Comparative Example 1 is substantially the same as that of Example 1, except that the lithium ion battery of Comparative Example 1 does not contain the first substance or the second substance.

[0224] [Comparative Example 2]

[0225] The preparation process of the lithium ion battery of Comparative Example 2 is substantially the same as that of Example 1, except that in the lithium ion battery of Comparative Example 2, the first substance is propylene.

[0226] [Comparative Example 3]

[0227] The preparation process of the lithium ion battery of Comparative Example 3 is substantially the same as that of Example 1, except that in the lithium ion battery of Comparative Example 3, the first substance phthalate is replaced by the second substance sodium chloride+polyethylene.

[0228] 2). Performance characterization of positive electrode sheets of lithium-ion batteries

[0229] 2.1) Measurement of polar functional groups: infrared spectroscopy to test characteristic functional groups;

[0230] 2.2) Measurement of slurry viscosity: It can be tested with a viscosity tester; the main principle of the viscosity tester is that the motor drives the rotor to rotate at a constant speed through variable speed. When the rotor rotates in the liquid, the liquid will generate a viscosity torque acting on the rotor, and the greater the viscosity torque, the greater the viscosity; the viscous torque acting on the rotor is detected by the sensor, and the viscosity of the measured liquid is obtained after computer processing.

[0231] 2.3) Measurement of compaction density: For details, refer to GB / T 24533-2009. Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, weigh the weight m of the powder, and set the pressure to 20MPa. The thickness (thickness after pressure relief) and volume v of the powder can be read on the equipment, and the compaction density can be calculated by ρ=m / v.

[0232] 2.4) Measurement of surface residual alkali: refer to GB / T 9736-2008 General method for determination of acidity and alkalinity of chemical reagents. Weigh 10-30g of positive electrode active material powder, add 100ml of pure water and stir for 30min, let it stand for 10min, filter and remove a certain amount of filtrate, select 0.05mol / L hydrochloric acid standard solution, drain the liquid to remove the bubbles in the burette, select the corresponding sensor and program to start the potentiometric titration test.

[0233] Table 1 Specific experimental parameters of Examples 1-20 and Comparative Examples 1-3

[0234]

[0235]

[0236]

[0237] 3). Lithium-ion battery performance characterization

[0238] 3.1) Measurement of crystallinity of binder: It can be tested by X-ray diffraction, density method, infrared spectroscopy, differential scanning calorimetry (DSC), etc. Taking X-ray diffraction as an example, the diffraction phenomenon of X-rays in crystals is used to obtain the characteristics of X-ray signals after diffraction, and the diffraction pattern is obtained after processing. By performing X-ray diffraction on the material and analyzing its diffraction pattern, if the crystalline scattering and non-crystalline scattering are separated from the diffraction pattern, the crystallinity is the ratio of the scattering of the crystalline part to the total scattering intensity. DSC test crystallinity: It is measured by quantifying the heat associated with polymer melting. The relative value is obtained by comparing with polymers of known crystallinity, or the heat is evaluated in the form of percentage of crystallinity by comparing with the melting heat of a 100% crystalline polymer sample.

[0239] 3.2) Measurement of positive electrode fracture: If cracks appear in the electrode that cannot be connected by naked eye observation, it is considered to be fractured;

[0240] 3.3) Brittleness of the positive electrode: Take the size as (4cm×25cm), i.e. 100cm 2 For the experimental samples, samples were taken along the TD direction, and the number of samples was ≥ 4; 2 The sample (folded in half along the longitudinal direction of 25cm) is pre-folded, and the pre-folded test film is placed on the plane of the test table, and rolled once with a 2kg cylindrical roller; the test sample is folded back along the longitudinal crease for a total of 4 times. The crease is observed against light, and if it is not light-transmissive (when the light-transmissive length of the crease is less than 10% of the crease length, it is considered an OK product), and if it is not broken, it is an OK product; if it is light-transmissive (when the light-transmissive length of the crease accounts for more than 10% of the crease length) or broken, it is an NG product.

[0241] Table 2 Performance tests of Examples 1-20 and Comparative Examples 1-3

[0242]

[0243]

[0244] In the embodiments of the present application, it is possible to determine whether the crystallinity of the first binder is reduced by the difference in crystallinity between the first binder and the second binder; when there is a difference in crystallinity between the first binder and the second binder, it means that the second binder is successfully modified, that is, the crystallinity of the first binder is reduced; the probability of the electrode sheet fracture can be determined by the positive electrode film layer and the slurry viscosity and the fracture condition of the positive electrode sheet. When the positive electrode sheet breaks after more folding layers, the brittleness of the positive electrode sheet is lower and the flexibility is better, and the possibility of the electrode sheet fracture is lower in the subsequent production process.

[0245] According to Examples 1-19 and Comparative Examples 1-3, when the first binder includes at least one of the polar functional groups in the first substance or the second substance, the crystallinity of the first binder, the slurry viscosity of the positive electrode film layer and the possibility of positive electrode sheet fracture can be reduced, thereby improving the toughness of the positive electrode sheet, which is beneficial to improving battery performance.

[0246] It can be seen from Examples 1-3 that various second binders containing fluorine segments can be applicable to the technical solution of the present application.

[0247] According to Examples 4 and 5 and Comparative Example 1, adding an inorganic filler in the first substance to the first binder can reduce the crystallinity of the binder, the slurry viscosity of the positive electrode film layer and the possibility of the positive electrode film layer breaking; further, adding an inorganic filler and an amorphous polymer in the first substance to the first binder can further reduce the crystallinity of the binder, the slurry viscosity of the positive electrode film layer and the possibility of the positive electrode film layer breaking.

[0248] According to Examples 4-6, a combination of multiple inorganic fillers and amorphous polymers to form a first substance added to the first binder can reduce the crystallinity of the first binder, the slurry viscosity of the positive electrode film layer, and the possibility of positive electrode film layer rupture.

[0249] It can be seen from Examples 1, 7-8 that a variety of second substances containing polar functional groups are suitable for the technical solution of the present application.

[0250] According to Examples 1, 9-16, by setting the mass ratio of the first substance or the second substance to the second binder to 0.005-0.2, especially 0.05-0.2, the crystallinity of the binder and the viscosity of the positive electrode film slurry can be reduced, and the positive electrode sheet has a lower possibility of fracture.

[0251] According to Examples 1, 9-14, setting the crystallinity of the first binder to 15%-45%, especially 20%-40%, can reduce the crystallinity of the binder and the viscosity of the positive electrode film slurry, and the positive electrode sheet has a lower possibility of fracture.

[0252] It can be seen from Examples 1, 17-18 that a variety of positive electrode active materials are suitable for the technical solution of the present application.

[0253] According to Examples 1, 19-20, by making the mass ratio of the surface residual alkali of the positive electrode active material to the positive electrode active material not exceed 0.05, especially not exceed 0.03, the crystallinity of the binder and the viscosity of the positive electrode film slurry can be reduced, and the positive electrode sheet has a lower possibility of fracture.

[0254] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode sheet, characterized in that: include: A positive electrode current collector and a positive electrode film layer provided on at least one side of the positive electrode current collector; The positive electrode film layer includes a positive electrode active material and a first binder, wherein the first binder includes at least one of a polar functional group or a first substance; Wherein, the first substance includes an inorganic filler and an amorphous polymer.

2. The positive electrode sheet according to claim 1, characterized in that: The first binder includes the first substance and a second binder; Wherein, the second binder includes a fluorine-containing segment.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The inorganic filler includes at least one of an oxide, a non-oxide with a dielectric constant greater than 3, and a non-oxide capable of transmitting active ions. Optionally, the inorganic filler includes at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The amorphous polymer includes at least one of polymethyl methacrylate and polyvinyl pyrrolidone.

5. The positive electrode sheet according to claim 1, characterized in that: The first binder includes a second binder substituted with a polar functional group at any position; Wherein, the second binder includes a fluorine-containing segment, and the second substance includes a polar functional group.

6. The positive electrode sheet according to claim 5, characterized in that: The second substance includes at least one of polyethers, lipids, and vinyls. Optionally, the second substance includes at least one of polyethers and lipids. Optionally, the second substance includes at least one of polyethylene oxide, phthalate, and polypropylene oxide-polyethylene oxide.

7. The positive electrode sheet according to claim 2 or 5, characterized in that: The mass ratio of the first substance or the second substance to the second binder is 0.005-0.

2. Optionally, the mass ratio of the first substance or the second substance to the second binder is 0.05-0.

2.

8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: The crystallinity of the first binder is 15%-45%. Optionally, the crystallinity of the first binder is 20%-40%.

9. The positive electrode sheet according to any one of claims 2 to 8, characterized in that: The second binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Optionally, the second binder includes polyvinylidene fluoride.

10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The positive electrode active material includes Li a Ni x Co y M 1-x-y O 2-b , wherein M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg and Nb, and optionally, M includes at least one of Mn, Al, B, Zr, Sr, W, Mg and Nb; 0.2≤a≤1.2, 0≤b≤0.2; 0.85≤x≤1, 0≤y≤0.15, optionally, 0.92≤x≤0.98, 0<y≤0.

08.

11. The positive electrode sheet according to claim 10, characterized in that: The mass ratio of the residual alkali on the surface of the positive electrode active material to the positive electrode active material is 0.0001-0.

05. Optionally, the mass ratio of the residual alkali on the surface of the positive electrode active material to the positive electrode active material is 0.0001-0.

03.

12. The positive electrode sheet according to any one of claims 1 to 11, characterized in that: When the positive electrode sheet is folded four times, the ratio of the light-transmitting length of the fold of the positive electrode sheet to the length of the fold of the positive electrode sheet is 0-0.

2. Optionally, the ratio of the light-transmitting length of the fold of the positive electrode sheet to the length of the fold of the positive electrode sheet is 0-0.

1.

13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: The slurry viscosity of the positive electrode film layer is 3000-20000 mPa·s. Optionally, the slurry viscosity of the positive electrode film layer is 5000-12000 mPa·s.

14. The positive electrode sheet according to any one of claims 1 to 13, characterized in that: The coating weight of the positive electrode sheet is 20-50 mg / cm 2 Optionally, the coating weight of the positive electrode sheet is 25-45 mg / cm 2 .

15. The positive electrode sheet according to any one of claims 1 to 14, characterized in that: The compaction density of the positive electrode sheet is 3-4 g / cm 3 Optionally, the compaction density of the positive electrode sheet is 3.2-3.6 g / cm 3 .

16. A method for preparing a positive electrode sheet, characterized in that: providing a positive electrode current collector; A positive electrode film layer is disposed on at least one side of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material and a first binder, wherein the first binder includes at least one of a polar functional group or a first substance; Wherein, the first substance includes an inorganic filler and an amorphous polymer.

17. The method according to claim 16, characterized in that The first binder includes at least one of a polar functional group or a first substance, including: providing the first substance and a second binder; Wherein, the second binder includes a fluorine-containing segment.

18. The method according to claim 16 or 17, characterized in that The inorganic filler includes at least one of an oxide, a non-oxide with a dielectric constant greater than 3, and a non-oxide capable of transmitting active ions. Optionally, the inorganic filler includes at least one of silicon dioxide, titanium dioxide, lithium niobate, and barium titanate.

19. The method according to claims 16 to 18, characterized in that The amorphous polymer includes at least one of polymethyl methacrylate and polyvinyl pyrrolidone.

20. The method according to claim 16, characterized in that The first binder includes at least one of a polar functional group or a first substance, including: Providing a second binder and a second substance, wherein the second binder and the second substance undergo a substitution reaction; Wherein, the second binder includes a fluorine-containing segment, and the second substance includes a polar functional group.

21. The method according to claim 20, characterized in that The second substance includes at least one of polyethers, lipids, and vinyls. Optionally, the first substance includes at least one of polyethers and lipids. Optionally, the second substance includes at least one of polyethylene oxide, phthalate, and polypropylene oxide-polyethylene oxide.

22. The method according to claim 17 or 20, characterized in that The mass ratio of the first substance or the second substance to the second binder is 0.005-0.

2. Optionally, the mass ratio of the first substance or the second substance to the second binder is 0.05-0.

2.

23. The method according to any one of claims 17 to 22, characterized in that The second binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. Optionally, the second binder includes polyvinylidene fluoride.

24. A battery cell, characterized in that: The invention comprises a positive electrode sheet as described in any one of claims 1 to 15 or a positive electrode sheet prepared by the method as described in any one of claims 16 to 23.

25. A battery, characterized in that: Comprising a plurality of battery cells as claimed in claim 24.

26. An electrical device, characterized in that: Comprising a battery as claimed in claim 25, the battery is used to provide electrical energy.

Citation Information

Patent Citations

  • Multilayer electrode for secondary battery, comprising binder having high crystallinity

    CN110431690A

  • Binder, preparation method, positive pole piece, secondary battery and electric device

    CN115133034A

  • Lithium secondary battery

    JP1998012243A

  • Electrode, lithium secondary battery using this electrode, electric double layer capacitor and el element

    JP1998064517A

  • Positive electrode active material slurry including rubber-based binder and positive electrode prepared therefrom

    US20160329566A1